Molten Salt Synthesis of Sr2Bi4Ti5O18 for Rhodamine B Removal via Adsorption-Photocatalysis Effect - Prasetyo, Anton; Bashofi, Syilfia Ainur Rohmah; Safitri, Widiya Nur; Hardian, Arie (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
The textile industry's rapid growth has increased dye waste; therefore, effective treatment solutions are needed. Photocatalysis technology has emerged as a promising approach due to its efficiency and environmentally friendly properties. Aurivillius-structured compounds have shown potential as photocatalysts because their ferroelectric properties can inhibit recombinant rate electron-hole. In this research, we synthesized Sr₂Bi₄Ti₅O₁₈ (one of the five-layer Aurivillius compound classes) using the molten salt method. Then, we tested its application for adsorption-photocatalysis degradation of rhodamine B. The diffractogram showed that the Sr2Bi4Ti5O18 phase was successfully synthesized with minor impurities (Bi2O3 and TiO2) attributed to incomplete reaction processes. The SEM image showed plate-like particles with non-uniform particle sizes was obtained. The Kubelka-Munk result showed that the band gap energy of Sr2Bi4Ti5O18 is 3.27 eV. Adsorption tests demonstrated that Sr2Bi4Ti5O18 reduced rhodamine B concentration by 52.5% for 30 minutes, which corresponds to its good adsorption capability. Further adsorption-photocatalysis experiments under light exposure showed 60% reduction in rhodamine B concentration for 60 minutes. The comparison between adsorption and photocatalysis results suggests that adsorption dominates in decreasing rhodamine B concentration. This is likely due to the large number of rhodamine B molecules adsorbed on the surface of Sr2Bi4Ti5O18, which prevents light from reaching the Sr2Bi4Ti5O18 surface, thereby hindering the degradation of rhodamine B through the photocatalysis mechanism.